Dekonstruksi Lakon Arjuna Wiwaha Dalam Pengajaran Semiotika Teater Bagi Pengembangan Kemampuan Berakting Mahasiswa - Pramulia, Pana; Budiyono, Sunu Catur; Prawoto, Eko Cahyo; Al Firdaus, Moh. Mujib (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2025)
This research aims to develop students' critical thinking, creativity, and acting skills through the application of semiotics and deconstruction theory in teaching theatre based on the play Arjuna Wiwaha. With a descriptive qualitative approach and a Project-Based Learning model using peer tutor techniques, students are invited to understand semiotic elements such as signs, symbols, and hidden meanings, and apply deconstruction theory to dismantle traditional assumptions in the story. The results showed that the students were able to identify themes, characters, and symbols, and integrate this understanding into the art of acting through dialogue, gesture, intonation, staging, and costume. The resulting theatre performances not only highlighted deep emotional conflicts and authentic characters, but also conveyed cultural values, philosophy of life, and moral dilemmas relevant to contemporary issues. The study concludes that this approach is effective in improving the quality of student acting while enriching theatre learning as a medium for cultural reflection and character building.